2022
DOI: 10.3233/jad-215244
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Machine Learning Approach with Neuropsychological Tests in Predicting Functional Impairment of Alzheimer’s Disease

Abstract: Background: In assessing the levels of clinical impairment in dementia, a summary index of neuropsychological batteries has been widely used in describing the overall functional status. Objective: It remains unexamined how complex patterns of the test performances can be utilized to have specific predictive meaning when the machine learning approach is applied. Methods: In this study, the neuropsychological battery (CERAD-K) and assessment of functioning level (Clinical Dementia Rating scale and Instrumental A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“… 50 The idea that semantic memory and other cognitive functions do not sustain task performance in a regular and constant way during the course of the whole testing minute is reflected by other procedural approaches to CFT scoring. Other than the aforementioned approach based on the characterization of the first 5 retrieved words, 56 , 58 other authors 68 have proposed splitting the global count into four sub-scores, each related to a 15-sec interval. This is to characterize task performance in a way that is more heterogeneous (as there is evidence that the earliest words are more dependent on automatic, rather than controlled semantic memory processing), 59 yet reliant on a scoring procedure that is of easy implementation.…”
Section: Alternative Measures Of Verbal Fluency Performancementioning
confidence: 99%
“… 50 The idea that semantic memory and other cognitive functions do not sustain task performance in a regular and constant way during the course of the whole testing minute is reflected by other procedural approaches to CFT scoring. Other than the aforementioned approach based on the characterization of the first 5 retrieved words, 56 , 58 other authors 68 have proposed splitting the global count into four sub-scores, each related to a 15-sec interval. This is to characterize task performance in a way that is more heterogeneous (as there is evidence that the earliest words are more dependent on automatic, rather than controlled semantic memory processing), 59 yet reliant on a scoring procedure that is of easy implementation.…”
Section: Alternative Measures Of Verbal Fluency Performancementioning
confidence: 99%
“…He presented the findings that linear models demonstrated superior performance with a relatively smaller sample size, whereas nonlinear models with low and high complexity exhibited improved accuracy with a larger dataset. 23 Notably, the nonlinear models showed a gradual increase in predictive accuracy, in particular when the sample size exceeded 500, emphasizing their effectiveness in exploiting complex patterns within the dataset. He suggested that nonlinear models, particularly with sufficient data, can predict levels of functional impairment, offering a valuable augmentation to the summary index of neuropsychological batteries, especially in estimating dementia-related functional status.…”
Section: Session 4 Recent Issues In Clinical Neuropsychologymentioning
confidence: 97%
“…It comprises a 2 min task to assess attention, a 2 min task to evaluate coordination, and a 4 min task to test memory, with a 30 s break in between. Additionally, research has demonstrated that ML algorithms, using neuropsychological, neurophysiological, and clinical data, have the ability to predict progression to MCI [33][34][35][36]. Notably, educational background has been found to be a factor that contributes to cognitive resilience, thus serving as a protective measure against the development of dementia.…”
Section: Neuropsychological Assessment and Clinical Datamentioning
confidence: 99%